Conflict, Violence and Peace - Harker, Christopher; Hörschelmann, Kathrin (Springer Singapore : Imprint: Springer, 2017)
This book broadens debates on violence, conflict and peace by examining the crucial role played by children and youth. Recent social, political and geographical research has demonstrated that children and youth are deeply impacted by war and violence and that, despite strong cultural assumptions about children's needs for protection, their wellbeing continues to be an afterthought rather than a central concern of global politics. Children and youth have also been shown to be more than just passive victims of violence. They are multiply enrolled in conflict as well as in the politics of reconciliation and peace. The handbook illustrates these complexities through a wide range of chapters that review key literatures on the topic from geographical perspectives and in diverse global contexts. Demonstrating the centrality of space for children and youth's positioning within, and responses to, violence and conflict, the chapters engage with novel conceptual approaches and up-to-date empirical research to develop nuanced understandings of different forms of violence in relation to global and local topographies of power and young people's subjectivities and agencies. While offering rich insights into context-specific dynamics, similarities and connections are also outlined between children and youth in the majority and minority world.
Keywords: Social sciences.; Sociology.; Childhood.; Adolescence.; Social groups.; Human geography.; elektronické knihy; electronic books